JSPS-8 Evaluation of ultrasonic cleaner and water resonance system apparatus for decontamination of Campylobacter and Salmonella on broiler carcasses in Thailand - N Phetsri; T Luangtongkum (Hemera Zoa, 2018)
Campylobacter and Salmonella are the leading causes of foodborne bacterial gastroenteritis in humans. Most diarrhea cases in Europe are caused by Campylobacter followed by Salmonella (1). Likewise, the majority of gastroenteritis cases in Japan are caused by Campylobacter (2). Since chicken meat consumption has been found to be associated with Campylobacter and/or Salmonella infection in humans, it is important to decontaminate these bacteria from chicken carcasses. Ultrasonic cleaner and water resonance system apparatus was developed to reduce Campylobacter and Salmonella residing in feather follicles of chicken carcass by using shock wave to remove microorganisms from follicles. It has been shown in Japan that this apparatus could be useful for decontamination of Campylobacter from chicken skin when it was used with chemical substances, such as sodium hypochlorite, cetylpi-ridinium chloride, etc. (3). However, it is unclear whether or not this apparatus can effectively reduce Campylobacter and Salmonella on chicken carcasses when it is used with potable water and/or other substances, such as organic acid. Therefore, the objective of this study is to evaluate the ability of ultrasonic cleaner and water resonance system apparatus in decontamination of Campylobacter and Salmonella on broiler chicken carcasses in Thailand.